POLITICAL TECHNOLOGIES OF LEGAL CULTURE EDUCATION - G. R. Absattarov (Scientific Journal of Pedagogy and Economics, 2019)
The article deals with the issues of political technologies of education of legal culture of the population, which have not yet been studied in political science. The article examines in more detail the forms, methods, techniques, methods and means of political technologies of education of legal culture of Kazakh people. On the basis of the conducted studies, it was concluded that the education of the legal culture of the population is carried out in Kazakhstan by: state bodies; special bodies ensuring the rule of law (prosecutor’s office, court, bodies of the ministries of justice, internal affairs, national security committee); party and public organizations; labor collectives; educational bodies, higher and secondary educational institutions, mass media and propaganda, creative unions and institutions of culture and art. At the same time, it should be said that political technologies, forms, methods, techniques and means of education of the legal culture of the population of Kazakhstan are mobile, they change depending on the political situation and changes in specific conditions and tasks, are improved with the advent of new political technologies. At the same time, the article focuses on the discussion issues.